SANDSTONE ROCK TYPING AND PERMEABILITY PREDICTION OF TELISA FORMATION FOR FIELD X - RAHADIAN ADI PUTRA (NIM : 22209088); Pembimbing : Prof. Ir. Pudji Permadi, M.sc., Ph. D., DEDY
The need of building a reliable reservoir model implies to the need of an accurate permeability prediction method as well. Unfortunately, most of the methods were lack developed based on intercorrelation between geological and engineering aspect of rocks, which explain how certain geological attributes, such as texture and mineralogy, will eventually affect the magnitude of permeability and porosity. The aim of this study was testing a new point of view, which was based on pore geometry and structure theory, on the two previous aspects intercorrelation. The sandstone Routine Core Analysis (RCAL), Special Core Analysis (SCAL) and geology report of Telisa Formation were used. There were 121 data sets of RCAL, 7 data sets of SCAL and geology report which consisted of photomicrograph and petrography analysis. Through rock type classification and permeability estimation method, the previous three data were integrated. Rock type classification was based on pore geometry, pore structure and core description, while permeability prediction was built based the correlation between permeability, porosity and irreducible water saturation. In this study, it was obtained eight rock types with distinct geological characteristics and they have been verified by SCAL data. The permeability estimation showed results that were close to cores permeability.